Awareness of Child Abuse and Neglect: A Prospective Interventional Study among Schoolteachers from Andhra Pradesh - Anuja Singaraju; Venkata Ratna Kumar Rudravaram; Sivakumar Nuvvula; Sreekanth Kumar Mallineni (MDPI AG, 2024)
Aim: To assess the awareness of schoolteachers from Andhra Pradesh towards child abuse and neglect (CAN) through pre- and post-educational intervention (audiovisual aid) questionnaires. Materials and methods: A cross-sectional study was conducted with 300 schoolteachers using a 12-item questionnaire that was created using the standard focus group discussion method. Baseline awareness of CAN was assessed using the questionnaire. Subsequently, all the schoolteachers were educated regarding the various types of CAN and the process of reporting CAN using an audiovisual aid. The same questionnaire was re-administered to all the teachers immediately after the intervention and after three months. The data were statistically analyzed using Fisher's exact test to compare the frequency and distribution of responses among the study participants at various intervals. Results: A statistically significant difference (p value < 0.05) was observed in the awareness of the schoolteachers regarding CAN compared to the baseline and immediately after the intervention. However, there was no statistically significant difference (p value > 0.05) between immediately after the intervention and three months. Conclusion: There is a need to have awareness among schoolteachers concerning CAN. However, after education through audiovisual aids, teachers' awareness of CAN has been improved.